Efektivitas Media Sosial Instagram Sebagai Media Promosi Pada UMKM Durian Woke: Studi Kasus Konten Digital Cafe Durian Woke Taktakan - Fernia Syafutri; Eri Handayani; Anggun Vebiyanti; Riki Gana Suyatna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Strengthening MSMEs in the face of globalization and intense competition means being able to respond to global challenges such as increasing product and service innovation. Consumers' willingness to buy and interest in products sold by MSMEs is increasing. The aim of this research is to determine the effectiveness of Durian Woke MSME product promotion on Instagram media. The effectiveness of advertising actions is measured using the AIDA concept (Attention, Interest, Desire, Action). The research sample consisted of 53 people with active Instagram accounts who followed the Durian Woke Instagram account in the food sector which advertises on Instagram media. The data collection method uses a questionnaire as respondent data. The research results show that the effectiveness of Instagram social media as an advertising medium is beneficial for Durian Woke MSMEs in stimulating consumer interest in finding out about available products.